Respostas

2013-11-20T22:23:59-02:00
a) -
Δ = b² -4ac 
Δ = 2² -4 *4 * (-5)
Δ = 4 + 80
Δ = 84
x' = (-b + √∆)/ 2a
(-2 + 9,16515138991168)/2 * 4

(-2 + 9,16515138991168)/8
7,16515138991168/8
0,89564392373896
x'' = (-b - √∆)/ 2a
(-2 - 9,16515138991168)/2 * 4
(-2 - 9,16515138991168)/8
-11,1651513899117/8
-1,39564392373896


b)
Δ = b² -4ac
Δ = (-12)² -4 *1 * 11
Δ = 144 -44
Δ = 100
x' = (-b + √∆)/ 2a
(-(-12) + 10)/2 * 1
(12 + 10)/2
22/2= 11
x'' = (-b - √∆)/ 2a
(-(-12) - 10)/2 * 1
(12 - 10)/2
2/2= 1

c)

Δ = b² -4ac
Δ = 3² -4 *2 * 0
Δ = 9 0
Δ = 9
x' = (-b + √∆)/ 2a
(-3 + 3)/2 * 2
(-3 + 3)/4
0/4= 0
x'' = (-b - √∆)/ 2a
(-3 - 3)/2 * 2
(-3 - 3)/4
-6/4= -1,5

.......